Research category and future development trend of data elements circulation and security - LI Fenghua; LI Hui; NIU Ben; QIU Weidong (Tongxin xuebao)
Towards the trend of evolution from controlled data sharing in the information technology era to ubiquitous circulation of data elements in the data technology era, the difference between data sharing and data element circulation was analyzed, what kind of data could become a data element was explained, and six attributes that data must have to become a data element were put forward. The data element circulation model and its primary links were defined, and the research scope of data element circulation was clarified. Furthermore, the relevant concepts of data element circulation were combed through, the important key technologies were analyzed, and the key technologies that need to be solved in the future were outlooked.